2018
DOI: 10.1017/s095026881800167x
|View full text |Cite
|
Sign up to set email alerts
|

Delay from symptom onset to treatment start among tuberculosis patients in England, 2012–2015

Abstract: Improving access to tuberculosis (TB) care and ensuring early diagnosis are two major aims of the WHO End TB strategy and the Collaborative TB Strategy for England. This study describes risk factors associated with diagnostic delay among TB cases in England. We conducted a retrospective cohort study of TB cases notified to the Enhanced TB Surveillance System in England between 2012 and 2015. Diagnostic delay was defined as more than 4 months between symptom onset and treatment start date. Multivariable logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 16 publications
8
10
1
Order By: Relevance
“…Delays are probably due to diagnostic challenges of a negative first-line investigation, but also because positive smear is associated with more severe and clinically and radiologically obvious disease [15][16][17]. Consistent with previous observational data from the UK or United States examining healthcare delay or total delay, we found longer delays in females [8,18,19], native-born cases [9,10,[18][19][20], cases with longer time since migration [19] and cases referred by general practitioners [10]. One explanation for the above populations experiencing longer delays would be a low index of clinical suspicion in the examining clinician for cases whom they perceive as being at low risk of TB.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Delays are probably due to diagnostic challenges of a negative first-line investigation, but also because positive smear is associated with more severe and clinically and radiologically obvious disease [15][16][17]. Consistent with previous observational data from the UK or United States examining healthcare delay or total delay, we found longer delays in females [8,18,19], native-born cases [9,10,[18][19][20], cases with longer time since migration [19] and cases referred by general practitioners [10]. One explanation for the above populations experiencing longer delays would be a low index of clinical suspicion in the examining clinician for cases whom they perceive as being at low risk of TB.…”
Section: Discussionsupporting
confidence: 88%
“…This may be further compounded for people with extrapulmonary sites of disease. Shorter delays to diagnosis have been noted in London compared to the lowest incidence areas of England, including the South East [19]; our findings are most generalisable to low-incidence settings with relatively low ethnic diversity, and similar referral pathways. Improving awareness of TB in such populations remains a significant challenge.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…We found that the diagnosis delay was longer in women (median = 27 days) than in men (median = 19 days). In a study performed in England, the diagnostic delay was found to be associated with being female [24]. In China, female sex was related with a risk of diagnostic delay [25,26].…”
Section: Discussionmentioning
confidence: 95%